2021
DOI: 10.1016/j.jid.2021.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Laminin 332 Is Indispensable for Homeostatic Epidermal Differentiation Programs

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…(b) A specific molecular network in the DEJ of infant and elderly skin At the molecular level, the DEJ contains a well-organized network of various proteins including laminin 332 (also called laminin V), types IV and VII collagens, heparan sulfate proteoglycan (perlecan) and nidogens. Laminin 332, a ligand of basal keratinocyte integrins, is essential for epidermal attachment in mice and humans (Rousselle et al, 1991(Rousselle et al, , 1997Nakano et al, 2002;Rousselle & Beck, 2013;Tayem et al, 2021). It has been reported to enhance hemidesmosome formation and reinforce the DEJ in skin-equivalent models (Amano, Nishiyama & Burgeson, 1999), but also to regulate the differentiation of mouse and human interfollicular epidermal stem cells which themselves produce laminin 332 (Yamada et al, 2018;Tayem et al, 2021), to inhibit sensory mechanotransduction and thereby decrease pain sensitivity in mice, and to control sensory axon branching behaviour (Chiang et al, 2011).…”
Section: Rasmussenmentioning
confidence: 99%
“…(b) A specific molecular network in the DEJ of infant and elderly skin At the molecular level, the DEJ contains a well-organized network of various proteins including laminin 332 (also called laminin V), types IV and VII collagens, heparan sulfate proteoglycan (perlecan) and nidogens. Laminin 332, a ligand of basal keratinocyte integrins, is essential for epidermal attachment in mice and humans (Rousselle et al, 1991(Rousselle et al, , 1997Nakano et al, 2002;Rousselle & Beck, 2013;Tayem et al, 2021). It has been reported to enhance hemidesmosome formation and reinforce the DEJ in skin-equivalent models (Amano, Nishiyama & Burgeson, 1999), but also to regulate the differentiation of mouse and human interfollicular epidermal stem cells which themselves produce laminin 332 (Yamada et al, 2018;Tayem et al, 2021), to inhibit sensory mechanotransduction and thereby decrease pain sensitivity in mice, and to control sensory axon branching behaviour (Chiang et al, 2011).…”
Section: Rasmussenmentioning
confidence: 99%
“…The LAMA3 gene belongs to the laminin family and is responsive to several epithelial-mesenchymal regulators, including keratinocyte growth factor, epidermal growth factor and skin fibrosis [ 28 ]. Previous studies found that targeted disruption of the LAMA3 gene causes junctional epidermolysis bullosa in many animals [ 29 , 30 , 31 ]. Based on this, we hypothesized that LAMA3 might affect the development of skin hair follicles through these pathways and further regulate cashmere traits.…”
Section: Resultsmentioning
confidence: 99%
“…Within the wound healing process, laminins play dual roles in re-epithelialization and angiogenesis, offering a scaffold for epithelial keratinocytes, facilitating their migration, and reinstating the intact epithelial barrier [30,31]. A surge in LM332 expression (Laminin α3β3γ2) by these keratinocytes is among the initial responses during wound reepithelialization post injury [32]. Healthy oral epithelium interfaces with implant or abutment surfaces, forming structures such as basal plates and hemidesmosomes.…”
Section: Discussionmentioning
confidence: 99%